Penanggulangan Pornografi dalam Mewujudkan Manusia Pancasila - Bunga, Dewi (Mahkamah Konstitusi Republik Indonesia, 2011)
The provisions concerning the prohibition of pornography are set in the national legal instruments and instruments of international law. Specifically regulated in Law no. 11 Year 2008 About Pornography whose existence was confirmed by the Constitutional Court Decision No. 10-17-23/PUU-VII/2009 who rejected the judicial review of Law no. 44 Year 2008 on Pornography seeing this legislation is still needed to protect public morality. Prohibition of pornography is also in line with the principle of the 2nd Pancasila who want a civilized human being. However, the existence of the rule is not effective in preventing pornography, especially with the internet presence that can expand and facilitate access to pornography. Therefore it is necessary efforts to control pornography in the human form of Pancasila.